Pengaruh Sudut Kontak Statis Terhadap Spreading Factor Dan Pada Bilangan Weber Tinggi - Muhsin Z. (Teknik Mesin "TEKNOLOGI", 2010)
An experimental of a single droplet impinging upon a hot surface at high Weber number has been conducted in the Laboratory of Fluids Mechanic Gadjah Mada University. Static contact angle was varied with three different modules, they were stainless steel with roughness (Ra) = 0.44μm; stainless steel coated with TiO2 without UV light and stainless steel coated with TiO2 with UV light. The static contact angle were founded; for stainless steel 84.6o; TiO2 without UV 36.6o and TiO2 with UV approximately 0o.Droplet substance was destilated water with initial diameter of 2.46 mm with Weber numbers were varied 98.6, 147.2, dan 197.2. Solid surface temperature were varied from 40oC-240oC by interval 20oC. Dynamics of the droplet on a solid  surface  were  recorded  using  high  speed  camera at 500 fps. As a result, the static contact angle influenced on spread characteristic after droplet impacting solid surface. Spreading factor increases with the decrease of static contact angle. Key words : droplet, Weber number, evaporation time, static contact angle, spreading factor